2020
DOI: 10.1101/2020.04.14.041467
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

From Value to Saliency: Neural Computations of Subjective Value under Uncertainty in PTSD

Abstract: Combat soldiers are vulnerable to Posttraumatic Stress Disorder (PTSD), following traumatic experiences in the battlefield. Studies have often used fear-related design to unravel the underlying neural deficits of learning and emotion regulation in PTSD patients. However, the role of individual uncertainty attitudes in the development of trauma-related psychopathology has hardly been examined, especially that uncertainty is highly related to the traumatic experiences from the battlefield. Through a monetary gam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 64 publications
1
2
0
Order By: Relevance
“…This can be interpreted as over-emphasized NVS and reduced engagement of the PVS in decision-making processes. Such imbalance between the two valence systems is in line with previous work in chronic PTSD patients reporting increased behavioral aversion to risky monetary gains and ambiguous monetary losses 24,26 . This further corresponds to the idea that trauma exposure might alter the homeostatic balance in motivation behavior towards less approach and more avoidance, which in turn might lead to the development of chronic PTSD 15 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This can be interpreted as over-emphasized NVS and reduced engagement of the PVS in decision-making processes. Such imbalance between the two valence systems is in line with previous work in chronic PTSD patients reporting increased behavioral aversion to risky monetary gains and ambiguous monetary losses 24,26 . This further corresponds to the idea that trauma exposure might alter the homeostatic balance in motivation behavior towards less approach and more avoidance, which in turn might lead to the development of chronic PTSD 15 .…”
Section: Discussionsupporting
confidence: 89%
“…symptom provocation, fearful faces) 18,19 among PTSD patients, potentially reflecting clinical symptoms of hyperarousal and intrusion (i.e., re-experiencing) 2023 . Furthermore, studies using decision-making tasks demonstrated an association between PTSD and increased behavioral aversion to risk 24,25 and ambiguous losses 26 , possibly reflecting the generalized (not only trauma-specific) oversensitivity of the NVS, often seen in PTSD patients. At the neural level, the role of the NVS in PTSD has been repeatedly documented as abnormally heightened amygdala activation and hyperactive salience network (e.g., anterior insula, dorsal anterior cingulate cortex) in response to negative stimuli 20,2729 .…”
Section: Introductionmentioning
confidence: 99%
“…Anticipatory ERP components (the cue-P3 and the SPN) were uniquely modulated by decision riskiness, whereas consummatory ERP components (the RewP and the fb-P3) were more affected by decision ambiguity. Given that forms of abnormal decision making are common across a variety of psychiatric and neurological disorders (Euteneuer et al, 2009;Jia et al, 2020;Pushkarskaya, Tolin, et al, 2015), our findings of the dissociable neural dynamics between risk and ambiguity should be extended to relevant clinical populations to facilitate a deeper understanding of their heterogenous mechanisms underlying uncertainty processing.…”
Section: Discussionmentioning
confidence: 98%